Analysis of Understanding and Awareness in the Implementation of Green Accounting in Sasirangan Household Industry MSMEs in Banjarmasin - Hikmahwati; Qalbiah, Nurul; Safrina, Noor (Ilomata International Journal of Management, 2025)
The production of Sasirangan fabric plays an important role in creating employment opportunities and preserving local culture amid modern market changes. However, behind these economic and cultural benefits lies a serious environmental concern, particularly due to the use of chemical dyes that generate wastewater potentially harmful to the river ecosystems in Banjarmasin City. This study aims to analyze the level of understanding and awareness among household-scale Sasirangan industry actors regarding the implementation of green accounting as an effort to manage environmental impacts. This research adopts a descriptive qualitative approach with a case study design. The study involved a population of 41 small-scale Sasirangan industry actors in Banjarmasin City. The data were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing/verification. The results show that most business owners and employees have limited understanding of green accounting, especially in terms of identifying and reporting environmental costs in financial statements. Although there is awareness of the environmental impact of chemical waste, concerns remain about the financial burden of managing waste or replacing harmful materials with environmentally friendly alternatives. These findings indicate a gap between environmental awareness and its practical application in business operations and financial reporting.